Two new species of the subgenus Stilobezzia (Stilobezzia) KIEFFER from Peruvian Amazonia (Diptera: Ceratopogoniade) - Cazorla, Carla Gisela (2005)
Adult and pupa of Stilobezzia (Stilobezzia) merceri CAZORLA & SPINELLI. n.sp. from Iquitos, and adult of Stilobezzia (S.) williamsi C. & S., n.sp. from Pagoreni, Cuzco. are described and illustrated. These species are compared with the similar congeners S. (S. ) bicolor LANE and S. (S) modesta LANE, and S. (S.) modesta LANE, and S.(S.) simplex LANE & FORATTINI, respectively.